153 Visuospatial and Executive Function in Adolescent Patients with Congenital Heart Disease. (October 2012) - Rhein, M von; Kugler, M; Latal, B
Abstract : Background and aims: Visuospatial deficits have been described for 8 year-old patients with congenital heart disease (CHD) after bypass surgery based on the performance in the Rey-Osterrieth complex figure test (ROCFT). It is unknown whether these deficits persist into adolescence and which scoring systems is optimal to score performance in the ROCFT. We therefore performed ROCFT in adolescent CHD patients and healthy controls, and compared performance according to three different scoring methods. Methods: We examined 53 adolescents (mean age 13.7 years, 44% male, 50% cyanotic CHD) with CHD after open-heart surgery (mean age at surgery: 1.4 years) and 32 healthy subjects. ROCFT was scored according to three different validated scoring methods. Results: Results varied markedly between the scoring methods. When scored according to Meyers & Meyers, patients performed significantly worse than controls in the copy task (p=0.03), whereas no significant differences were found in the memory task. Scoring according to Wallon and Mesmin showed clear differences between subjects and controls with respect to the approach how to construct the figure: 78% of CHD patients (controls: 47%) displayed a unstructured or intermediate approach to drawing the figure, whereas only 22% of CHD patients (controls: 53%) chose a complex approach (p=0.001). Scoring according to Bernstein et al. showed no differences between groups. Conclusions: Adolescents with surgically treated CHD demonstrate deficits in visuospatial and executive function. The ROCFT provides information on different functional aspects, which cannot adequately be assessed with one single scoring method.